Is the Subject the Locus of Muslim Ethics? Relocating the Ethics of Tithing in the Transnational Shi‘i Community - Blanch, Samuel David (Islam and Christian-Muslim relations, 2022)
This article offers a critique of the descriptive power of subjectivity in studies of contemporary Muslim ethics. After Saba Mahmood and others, subjectivity has become perhaps the dominant analytical tool for the description of the ethical qualities of modern religious life. It is responsive to both the reflexivity held to be newly characteristic of modernity, and to the need to allow for the sheer diversity of modern religious life. However, through a multisite ethnographic study of the Shi‘i Muslim khums, an obligatory 20% ‘tithe’ or tax on annual income, the article argues that approaches to ethics in terms of subjectivity have been insufficiently attentive to the ethical gravity of the thing itself. The special characteristics of khums payment, administration and disbursement between fieldsites in Australia and Iran, serve to foreground issues neglected in a literature that has focused almost entirely on a Sunni ‘orthopraxy’. Methodologically, the article argues for a greater attentiveness to the materiality of the things of ethics and, conceptually, for a shift towards relations between persons and things as the locus of ethical investigation.